2017
DOI: 10.1093/ehjci/jex160
|View full text |Cite
|
Sign up to set email alerts
|

Multi-centre study of whole-heart dynamic 3D cardiac magnetic resonance perfusion imaging for the detection of coronary artery disease defined by fractional flow reserve: gender based analysis of diagnostic performance

Abstract: Whole-heart dynamic 3D CMR stress perfusion imaging has a high diagnostic accuracy for the detection of significant CAD irrespective of gender and is therefore a suitable non-invasive testing tool to detect myocardial ischaemia in both genders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…However, no single noninvasive method has yet reached clinical applicability in terms of enabling a reliable diagnosis of microvascular ischemia. In current clinical practice, the diagnosis of microvascular ischemia is based on the presence of myocardial ischemia on functional perfusion imaging, i.e., MRI 35 37 , CTP 38 , or positron emission tomography (PET) 39 , in the absence of coronary stenosis on either coronary angiography including an option for acetylcholine testing 40 or CCTA, which has high diagnostic accuracy for noninvasive detection of macrovascular CAD 41 , 42 . While the pathophysiological relation between epicardial vessel wall remodeling and resultant pathophysiological consequences for myocardial blood flow (MBF) has been studied 43 , imaging of the microcirculation remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…However, no single noninvasive method has yet reached clinical applicability in terms of enabling a reliable diagnosis of microvascular ischemia. In current clinical practice, the diagnosis of microvascular ischemia is based on the presence of myocardial ischemia on functional perfusion imaging, i.e., MRI 35 37 , CTP 38 , or positron emission tomography (PET) 39 , in the absence of coronary stenosis on either coronary angiography including an option for acetylcholine testing 40 or CCTA, which has high diagnostic accuracy for noninvasive detection of macrovascular CAD 41 , 42 . While the pathophysiological relation between epicardial vessel wall remodeling and resultant pathophysiological consequences for myocardial blood flow (MBF) has been studied 43 , imaging of the microcirculation remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…78 Whole--heart dynamic CMR perfusion is based on a new 3D acquisition sequences that allow readout of the entire examination volume at once in contrast to routinely used 2D acquisition of separate slices. [78][79][80][81][82][83][84] Hybrid imaging holds promise for the field of cardiac imaging and planning of myocardial revascularization. It may be of particular value in multivessel disease, where the simultaneous…”
mentioning
confidence: 99%
“…In a study by Hamada et al, 27 whole‐heart 3‐D perfusion MRI demonstrated high diagnostic accuracy for significant CAD irrespective of gender. Notably, they showed a high sensitivity of 89% and NPV of 90% for female populations, which are often considered to be an undertreated demographic 27 . The disadvantages of current 3‐D MR perfusion techniques include the relatively poor in‐plane spatial resolution (2.3 × 2.3 mm 2 ) and the long temporal footprint 28 .…”
Section: Discussionmentioning
confidence: 97%